Peran Orang Tua Dalam Motivasi Belajar Anak Di Rumah - Nia Afrilda Nasution; Dwi Anatasia Br. Ginting; Imam Sholeh Rambe; Syahrial Syahrial (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The role of parents in supporting children's learning in the home environment has a substantial impact on children's academic, emotional, and social progress. Starting from the early stages of development, parents' involvement in supporting their children's learning process at home, along with the strategies they implement, plays a crucial role in achieving this goal efficiently. This research applies the literature study method to explore how parents inspire their children to study at home. The research results emphasize the urgency of the role of parents in triggering children's enthusiasm for learning in the home environment. They are not only providers of learning materials, but also as models and facilitators who influence their children's attitudes and enthusiasm for learning. These findings are in line with learning motivation theories which highlight the influence of social and environmental factors in shaping children's enthusiasm for learning internally and externally. Thus, this research emphasizes that parents have an important role in shaping children's learning attitudes and behavior at home. Therefore, it is important for parents to understand their role in stimulating children's enthusiasm for learning at home and to get support in improving the skills needed in this regard.purpose.